2015
DOI: 10.1002/chin.201508012
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Noble‐Metal‐Free, Tetra‐Nickel Polyoxotungstate Catalyst for Efficient Photocatalytic Hydrogen Evolution.

Abstract: A Noble-Metal-Free, Tetra-Nickel Polyoxotungstate Catalyst for Efficient Photocatalytic Hydrogen Evolution. -Na 6K4[Ni4(H2O)2(PW9O34)2]·32H2O is synthesized by refluxing an aqueous solution of Na 2WO4, Na2HPO4, and Ni(OAc)2 for 2.5 h, followed by addition of KOAc (73% yield). The compound crystallizes in the triclinic space group P1 with Z = 1 (single crystal XRD). The structure contains a tetra-nickel cluster core [Ni 4O14], which is sandwiched by two trivacant, heptadentate [PW9O34] 9ligands. The material wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…[63][64][65][66] More recently this strategy has garnered considerable interest in the field of water oxidation, where the work of Hill and Bonchio in particular, has demonstrated how catalytically active transition metal substituted POM clusters can be sensitized in the presence of the [Ru II (bpy)3] 2+ chromophore and a sacrificial oxidant in order to drive the oxidation of water under visible light irradiation. [67][68][69][70][71] Interestingly, the same approach can also be used to drive the corresponding hydrogen-reduction half-reaction, 72,73 and new studies have even shown how this strategy can be combined with supramolecular, self-assembly and materials design approaches to generate next-generation photocatalytic porous framework materials, 74,75 which may help to mitigate some of the more common disadvantages of class I hybrids, discussed below.…”
Section: Considerations In Hybrid-pom Classificationmentioning
confidence: 99%
“…[63][64][65][66] More recently this strategy has garnered considerable interest in the field of water oxidation, where the work of Hill and Bonchio in particular, has demonstrated how catalytically active transition metal substituted POM clusters can be sensitized in the presence of the [Ru II (bpy)3] 2+ chromophore and a sacrificial oxidant in order to drive the oxidation of water under visible light irradiation. [67][68][69][70][71] Interestingly, the same approach can also be used to drive the corresponding hydrogen-reduction half-reaction, 72,73 and new studies have even shown how this strategy can be combined with supramolecular, self-assembly and materials design approaches to generate next-generation photocatalytic porous framework materials, 74,75 which may help to mitigate some of the more common disadvantages of class I hybrids, discussed below.…”
Section: Considerations In Hybrid-pom Classificationmentioning
confidence: 99%
“…And there is no significant decrease in the catalytic activity for sample CoPW 9 in the presence of mercury (see Figure S5) [12]. The results suggest that sample CoPW 9 is an efficient homogeneous catalyst for the H 2 evolution from water splitting.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…They suffer from the problems of either limited solubility in aqueous media, instability toward strong acidic environments, or they deactivate by ligands dissociation, decomposition and/or hydrogenation [12]. Therefore, discovery of homogenous catalyst, without organic ligands, based on earth-abundant cobalt element would be highly useful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation